New insights into the inter-organ crosstalk mediated by ChREBP - Carbinatti, Thais; Régnier, Marion; Parlati, Lucia; Benhamed, Fadila; Postic, Catherine (Frontiers in Endocrinology, 2023)
Carbohydrate response element binding protein (ChREBP) is a glucose responsive transcription factor recognized by its critical role in the transcriptional control of glycolysis and de novo lipogenesis. Substantial advances in the field have revealed novel ChREBP functions. Indeed, due to its actions in different tissues, ChREBP modulates inter-organ communication through secretion of peptides and lipid factors, ensuring metabolic homeostasis. Dysregulation of these orchestrated interactions is associated with development of metabolic diseases such as type 2 diabetes (T2D) and non-alcoholic fatty liver disease (NAFLD). Thus, we recapitulate the current knowledge about ChREBP-mediated inter-organ crosstalk through secreted factors and its physiological implications. As the liver is considered a crucial endocrine organ secreting hepatokines, we will focus in this review on the role of ChREBP-regulated hepatokines. Lastly, we will discuss the involvement of ChREBP in the progression of metabolic pathologies, as well as how the impairment of ChREBP-dependent signalling factors contributes to the onset of such diseases.